2012
DOI: 10.1007/s00380-012-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Blunted heart rate recovery is associated with exaggerated blood pressure response during exercise testing

Abstract: Increased sympathetic activity and endothelial dysfunction are the proposed mechanisms underlying exaggerated blood pressure response to exercise (EBPR). However, data regarding heart rate behavior in patients with EBPR are lacking. We hypothesized that heart rate recovery (HRR) could be impaired in patients with EBPR. A total of 75 normotensive subjects who were referred for exercise treadmill test examination and experienced EBPR were included to this cross-sectional case-control study. The control group con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…However, when measured within 3 min after exercise, PR was not significantly different among the 3 groups, despite differences in their age-related maximum heart rate. This phenomenon may be explained by the age-related decline of cardiac vagal tone [33,34], and the recovery in PR after the exercise stress test, which has gained general acceptance [35]. Thus, PR in the younger age group after exercise would recover to baseline faster than that in the older age group.…”
Section: Discussionmentioning
confidence: 96%
“…However, when measured within 3 min after exercise, PR was not significantly different among the 3 groups, despite differences in their age-related maximum heart rate. This phenomenon may be explained by the age-related decline of cardiac vagal tone [33,34], and the recovery in PR after the exercise stress test, which has gained general acceptance [35]. Thus, PR in the younger age group after exercise would recover to baseline faster than that in the older age group.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanisms contributing to EBP are not fully understood, but contributing factors may include enhanced sympathetic nervous system activity (12,14,31), greater LV mass (2,20,34) and myocardial dysfunction (47), endothelial dysfunction (4,44), increased central arterial stiffness (2,42), and a heightened metaboreflex (31). We previously demonstrated no differences in LV mass, sympathetic reactivity to static exercise and the metaboreflex response between athletes with and without EBP (11).…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, the EBP response has been associated with enhanced sympathetic activity (12,14,31), an enhanced metaboreflex (31), and resting cardiovascular dysfunctions including central arterial stiffness (2,42) and elevated left ventricular mass (2,20,34), all of which are postulated to contribute to cardiovascular morbidity later in life. We recently demonstrated that middle-aged endurance trained athletes with EBP do not exhibit these resting cardiovascular and sympathetic dysfunctions (11).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise induced hypertension is defined as an increase in SBP >210 mmHg for men and >190 mmHg for women [192][193][194][195][201][202][203][204][205]]. An increase of DBP more than 10 mmHg above the resting value or an absolute value of 90 mmHg also is considered abnormal and could predict increased likelihood of CAD.…”
Section: Blood Pressure (Bp) Abnormalitiesmentioning
confidence: 99%
“…A resting SBP >200 mmHg and DBP >110 mmHg are considered relative contraindications to EST. Exercise induced hypertension may indicate an increased risk for future hypertension, left ventricular hypertrophy, and cardiovascular events [192][193][194][195][201][202][203][204][205]209]. In the Coronary Risk Development in Young Adults cohort, participants with exercise-induced hypertension were 1.7 times more likely to have developed hypertension at 5-year follow- up than those with a normal response.…”
Section: Blood Pressure (Bp) Abnormalitiesmentioning
confidence: 99%